2023
DOI: 10.3389/fnhum.2023.1197459
|View full text |Cite
|
Sign up to set email alerts
|

The cerebellum and cognitive neural networks

Abstract: Cognitive function represents a complex neurophysiological capacity of the human brain, encompassing a higher level of neural processing and integration. It is widely acknowledged that the cerebrum plays a commanding role in the regulation of cognitive functions. However, the specific role of the cerebellum in cognitive processes has become a subject of considerable scholarly intrigue. In 1998, Schmahmann first proposed the concept of “cognitive affective syndrome (CCAS),” linking cerebellar damage to cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 100 publications
3
8
0
Order By: Relevance
“…Our results are consistent with the current knowledge on the involvement of the cerebellum in language processing (De Smet et al, 2007; Mariën & Beaton, 2014; Zhang et al, 2023). The left VI cerebellar lobule that we report is known to be functionally connected to SMN at rest and involved in motor tasks (Guell et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with the current knowledge on the involvement of the cerebellum in language processing (De Smet et al, 2007; Mariën & Beaton, 2014; Zhang et al, 2023). The left VI cerebellar lobule that we report is known to be functionally connected to SMN at rest and involved in motor tasks (Guell et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…The human cerebellum represents a structure of the brain located at the lower back of the brain, underlying the occipital and temporal lobes . As a highly specialized region, the cerebellum encompasses approximately 80% of the total brain neurons and regular arrays of neuronal units and consists of two main types of cells: cerebellar cortical neurons responsible for regulating, connecting, and maintaining higher cognitive functions, and deep cerebellar neurons accountable for basic muscle coordination …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed the engagement of the cerebellum in a variety of processes, including motor functions such as maintaining body equilibrium, controlling muscle tension, and coordinating deliberate movements, as well as cognitive activities, emotional experiences, and social interactions. , Damage to the cerebellum frequently leads to impairment, which impacts (i) the visuospatial abilities, attention, in particular focusing attention on space and time; (ii) executive functions such as inhibitory control, cognitive flexibility, planning, reasoning, and decision-making; (iii) the working memory affecting comprehension, reading, and learning; (iv) language skills, including issues related to the timing, adaptation, prediction, planning, fluency, grammar, or even speech disruptions . Also, the cerebellar dysfunctions induced by modifications at the molecular level represent the basis of the common pathological conditions such as Parkinson’s disease (PD), Huntington disease (HD), Alzheimer’s disease (AD), and multiple sclerosis (MS) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations